2015
DOI: 10.1515/bejeap-2014-0079
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pharmacies’ Right to Negotiate Discounts on the Market Share of Parallel Imported Pharmaceuticals

Abstract: This paper analyzes how allowing pharmacies to negotiate discounts with parallel traders and producers affects the market share for parallel imports. Economic theory predicts that discount negotiations will promote products bought directly from the producers because producers have cost advantages, due to which they always underbid the marginal prices of parallel traders. A reform that allowed discount negotiations is found to reduce the market share for parallel imports by about 11 percentage points to reach 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
(33 reference statements)
1
4
0
Order By: Relevance
“…For all IV− specifications, the null hypothesis that the model is under− identified is rejected at the 1% significance level; and the null hypothesis for the Hansen J test that the instruments are valid-uncorrelated with the error term-are not rejected at conventual levels discounts to pharmacies. Results in Granlund (2015) are consistent with producers after July 2009 giving pharmacies discounts to incentivize them to sell locally sourced products instead of parallel imports. It is also possible that producers, due to the possibility of giving discounts, stopped decreasing list prices in response to facing competition from parallel imports.…”
Section: Appendix 1: Validity Of Instrumentssupporting
confidence: 68%
See 1 more Smart Citation
“…For all IV− specifications, the null hypothesis that the model is under− identified is rejected at the 1% significance level; and the null hypothesis for the Hansen J test that the instruments are valid-uncorrelated with the error term-are not rejected at conventual levels discounts to pharmacies. Results in Granlund (2015) are consistent with producers after July 2009 giving pharmacies discounts to incentivize them to sell locally sourced products instead of parallel imports. It is also possible that producers, due to the possibility of giving discounts, stopped decreasing list prices in response to facing competition from parallel imports.…”
Section: Appendix 1: Validity Of Instrumentssupporting
confidence: 68%
“…On average during the study period, USD 1 = SEK 7.52 and EUR 1 = SEK 9.20. 10 Physicians and pharmacists oppose substitution for only 2-3% of the observations each (Dental and Pharmaceutical Benefits Agency, 2016;Granlund, 2015). 7 Three percent of the groups of exchangeable products includes more than one locally sourced brandname product.…”
Section: Parallel Imports the Pharmacy Monopoly And The Benefit Schemementioning
confidence: 99%
“…There is a potential endogeneity problem because the error term, ɛ e , t , can be correlated with price differences between the lowest bidder and other products. High price differences might in turn affect Sw e , t positively, by making it more expensive for consumers to buy another alternative, or negatively, because pharmacies tend to be more inclined to sell expensive products the more they earn by doing so (Brekke, Holmås and Straume, ; Granlund, ). To address the potential endogeneity of Sw e , t , we estimate a specification, using Sw, instead of SwP and NotPolicy, with 2SLS and, using OLS as a comparison.…”
Section: Empirical Specificationsmentioning
confidence: 99%
“…This strengthens the conjecture that the preference of locally sourced product sellers to compete with parallel imports by giving discounts to pharmacies is a main reason that previous studies [6][7][8] have not found significant effects on list prices when discounts were legal. Some advantages of using discounts are that they can be quickly reverted and do not affect the maximum prices producers are allowed to charge in countries that use external reference pricing [18].…”
Section: Discussionmentioning
confidence: 99%